Answer:
3x - 4y + 22 = 0
Step-by-step explanation:
The equation of a straight line passing through the given two points ([tex]x_{1},y_{1}[/tex]) and ([tex]x_{2},y_{2}[/tex]) is given by the formula
[tex]\frac{y - y_{1} }{y_{1} - y_{2}} = \frac{x - x_{1} }{x_{1} - x_{2}}[/tex]
Here in our case, the two given points are (-6,1) and (-2,4) and the equation of the straight line passing through those two points will be
[tex]\frac{y - 1}{1 - 4} = \frac{x - (- 6)}{- 6 - ( - 2)}[/tex]
⇒ 4(y - 1) = 3(x + 6)
⇒ 3x - 4y + 22 = 0 (Answer)